Glycemic effects of vildagliptin and metformin combination therapy in Indian patients with type 2 diabetes: An observational study (印度2型糖尿病患者使用维格列汀与二甲双胍联合治疗对血糖的影响：一项观察性研究). (27th August 2013) - Chatterjee, Sanjay; Chatterjee, Sudip
Abstract Background To analyze the glycemic response of Indian patients with type2 diabetes mellitus (T2DM) to combination therapy with vildagliptin and metformin and compare our data with those of clinical trials. Methods In a retrospective study of the hospital database, the glycemic control of 280 patients with T2DM who were either on a once‐ or twice‐daily regimen of combination therapy with vildagliptin 50 mg and metformin 500 mg was analyzed. Results The mean duration of follow‐up of the patients was 16.8 months. There was a reduction in fasting plasma glucose (FPG) of 1.52 ± 0.79 and 1.88 ± 0.87 mmol/L in the once‐ and twice‐daily groups, respectively (both P < 0.0001) from baseline to last visit. The reduction in postprandial plasma glucose (PPPG) in the once‐ and twice‐daily groups was 3.98 ± 1.72 and 4.33 ± 1.88 mmol/L, respectively (both P < 0.0001), whereas the reduction in HbA1c was 1.41 ± 1.39% and 1.90 ± 1.49%, respectively (both P < 0.0001). The differences in the reductions achieved in FPG and HbA1c with the two dosing regimens were significant. Conclusion Although the present retrospective study shows a robust response to the combination of vildagliptin and metformin in Indian patients, more multicenter studies from India with a greater number patients are necessary to confirm this finding.